2002
DOI: 10.1046/j.1365-2168.2002.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended preservation of non-heart-beating donor livers with normothermic machine perfusion

Abstract: Warm ischaemia for 1 h and simple cold storage (UW solution) for 24 h renders the liver non-viable. Oxygenated, sanguinous perfusion as a method of preservation recovers liver function to a viable level after 24 h of preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 14 publications
7
144
0
1
Order By: Relevance
“…Given the complexity and financial burden of a large animal transplantation model, a simulation phase was used to explore our hypothesis, as done previously by other authors (9,10). Innate and adaptive immune responses subsequent to IRI are possible only if all cells are released from compartments such as the spleen, lymph nodes and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the complexity and financial burden of a large animal transplantation model, a simulation phase was used to explore our hypothesis, as done previously by other authors (9,10). Innate and adaptive immune responses subsequent to IRI are possible only if all cells are released from compartments such as the spleen, lymph nodes and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also proposed the use of techniques of extracorporeal machine donor perfusion instead of cold storage, as it has been reported that NHBD grafts are more susceptible to cold ischemia that is preceded by warm ischemia in this type of donor. [25][26][27] We believe that progress in this field will be critical to expanding the utilization of UNHBDs.…”
Section: Discussionmentioning
confidence: 99%
“…St Peter et al 12 used a pig model to discover that DCD livers undergoing normothermic machine perfusion recovered liver function significantly better than livers in cold storage. Livers were subjected to 1 hour of warm ischemia before preservation.…”
Section: Commentsmentioning
confidence: 99%